Financial reforms and innovation: A micro-macro perspective - Spyridon Boikos; Ioannis Bournakis; Christopoulos Dimitris; Peter McAdam (European Central Bank (ECB), 2021)
We develop a horizontal R&D growth model that allows us to investigate the different channels through which financial reforms affect R&D investment and patent activity. First, a "micro" reformthat abolishes barriers to entry in the banking sector produces a straightforward result: a decrease in lending rates which stimulates R&D investment and economic growth. Second, a "macro" reform that removes restrictions on banks' reserves and credit controls. While this reform increases liquidity, it also increases the risk of default, potentially raising the cost of borrowing. This we dub the "reserves paradox" - this makes banks offset the rise in the default rate with a higher spread between loans and deposit rates. Thus our model suggests that whilst micro reforms boost innovation, macro reforms may appear negative. We test and find empirical support for these propositions using a sample of 21 OECD countries.
Keywords: G2; C23; E44; O43; 330; Finance; Growth; Patents; Monitoring; Reserves Paradox; Estimation